Hydrogen peroxide and viral infections: A literature review with research hypothesis definition in relation to the current covid-19 pandemic (2020)
We reviewed the literature concerning the innate response from nasal and oral epithelial cells and their reaction to hydrogen peroxide (H2O2). Hydrogen peroxide is produced physiologically by oral bacteria and plays a significant role in the balance of oral microecology since it is an important antimicrobial agent. In the epithelial cells, the enzyme superoxide dismutase catalyzes a reaction leading from hydrogen peroxide to the ion superoxide. The induced oxidative stress stimulates a local innate response via activation of the toll-like receptors and the NF-κB. Those kinds of reactions are also activated by viral infections. Virus-induced oxidative stress plays an important role in the regulation of the host immune system and the specific oxidant-sensitive pathway is one of the effective strategies against viral infections. Therefore, nose/mouth/throat washing with hydrogen peroxide may enhance those local innate responses to viral infections and help protect against the current coronavirus pandemic. We strongly encourage the rapid development of randomized controlled trials in both SARS-CoV-2 positive and negative subjects to test the preliminary findings from the in-vitro and in-vivo observational studies that we identified.